PENGARUH UJI KOMPETENSI WARTAWAN (UKW) TERHADAP PROFESIONALISME WARTAWAN DI PEKANBARU - Nila Jumiatri Asman; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Journalists are required to be able to take responsibility for all their journalistic activities before the public and the press. Due to the large number of complaints among media users who rate journalists as often misquoted, the news is inaccurate or even twists the news. Therefore, the press council in 2010 echoed journalist competency improvement through the Journalist Competency Test (UKW). One of the objectives of the journalists' competencies is to improve the quality and professionalism of journalists. However, even after the formation of this competency, cases and complaints to the press council relatively increased. The Social Responsibility Theory assumes that freedom has a value commensurate with responsibility for that freedom. This theory also encourages professionalism and high standards of achievement for journalists in carrying out their journalistic duties. The purpose of this study was to determine how much influence the Journalist Competency Test (UKW) has on the Professionalism of Journalists in Pekanbaru.The method used in this research is quantitative explanative. Research data collection using questionnaires and documentation. The sample in this study amounted to 124 respondents using accidental sampling techniques. This research was conducted in three institutions in Pekanbaru that had been verified by the Press Council, including PWI, AJI and IJTI. The analysis test used in this study is a simple linear regression analysis and to process the questionnaire data, carried out using SPSS for Windows version 23.The results obtained from the simple linear regression analysis in this study were Journalist Competency Test (UKW) which influenced Journalist Professionalism by 51.2%. While the other 48.8% is influenced by other factors outside of this study. However, the relationship between Journalist Competency Test (UKW) and Journalism Professionalism is included in the strong category with a value of 0.715. The significance value in this study was 0,000 <0.05 (significant level of significance) with a t count of 11.303.